Muslims and Jews in Medieval Portugal: Interaction and Negotiation (Fourteenth – Fifteenth Centuries) - Barros, Maria Filomena Lopes de (2021)
The parameters of interaction between Jews and Muslims in the Portuguese kingdom—both at the institutional and personal levels—reflect, and are reflected on, a social and mental structure originating in the construction of a respublica christiana, in which they took part not only as subjects but also as objects of the ideological discourse which defined the Christian community itself. As real, non-idealized individuals, they participate in a shared life which includes the three religions. Although different and physically separated from each other, as institutional entities, Jewish and Muslim comunas necessarily converge on common political options, in a society where, especially from the fourteenth century onwards, inter-confessional boundaries become crystallized in laws which progressively favour the segregation of alterity. Such boundaries, nonetheless, are constantly crossed in everyday life, with the interaction between Christians, Jews, and Muslims proving indispensable to the very survival of a community, in the broadest sense of the term.